The Influence of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on the Performance of Employees of the Istiqlal Mosque Management Agency - Dudung Hadiwijaya; Endang Suherna (JMB : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of intellectual, emotional, and spiritual intelligence on employee performance at the Istiqlal Mosque Management Agency. Based on the t-test results, it was found that all three independent variables—Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence—have a significant effect on employee performance, with significance values of 0.000 (< 0.05) and t-calculated values exceeding the t-table value (1.978). Intellectual Intelligence contributes 32.5% to performance and shows a moderate correlation, while Emotional Intelligence has the strongest influence with a contribution of 41.8% and a strong correlation. Spiritual Intelligence also demonstrates a strong relationship with performance, contributing 37.4%.. Furthermore, the F-test results show that intellectual, emotional, and spiritual intelligence simultaneously have a significant impact on employee performance, with an F-calculated value of 66.377 > F-table value of 2.67 and a significance value of 0.000. Statistically, the combined contribution of these three variables to employee performance is 59.8%, while the remaining 40.2% is influenced by other factors beyond the scope of this study, such as work environment, leadership, organizational culture, or other personal factors